2020
DOI: 10.1007/s10393-020-01507-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Predicts Exposure to Respiratory Infection in a Wild Chimpanzee Group

Abstract: Respiratory pathogens are expected to spread through social contacts, but outbreaks often occur quickly and unpredictably, making it challenging to simultaneously record social contact and disease incidence data, especially in wildlife. Thus, the role of social contacts in the spread of infectious disease is often treated as an assumption in disease simulation studies, and few studies have empirically demonstrated how pathogens spread through social networks. In July-August 2015, an outbreak of respiratory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 103 publications
(142 reference statements)
3
20
0
Order By: Relevance
“…Nevertheless, respiratory disease is a major cause of morbidity and mortality in both captive and wild primate populations and thus a prominent threat to general primate welfare [ 40 , 42 , 43 , 54 , 55 , 56 ]. To date, only two studies have investigated the link between SNA measures and the occurrence of respiratory disease in primates [ 57 , 58 ]. One study found no association between the social network and respiratory disease in mountain gorillas ( Gorilla beringei beringei ) [ 57 ], while another study showed that in chimpanzees, males with higher strength in a proximity network had a higher chance of showing symptoms of respiratory disease, indicating the vital role of the social-proximity network in the spread of the pathogen in the group [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, respiratory disease is a major cause of morbidity and mortality in both captive and wild primate populations and thus a prominent threat to general primate welfare [ 40 , 42 , 43 , 54 , 55 , 56 ]. To date, only two studies have investigated the link between SNA measures and the occurrence of respiratory disease in primates [ 57 , 58 ]. One study found no association between the social network and respiratory disease in mountain gorillas ( Gorilla beringei beringei ) [ 57 ], while another study showed that in chimpanzees, males with higher strength in a proximity network had a higher chance of showing symptoms of respiratory disease, indicating the vital role of the social-proximity network in the spread of the pathogen in the group [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only two studies have investigated the link between SNA measures and the occurrence of respiratory disease in primates [ 57 , 58 ]. One study found no association between the social network and respiratory disease in mountain gorillas ( Gorilla beringei beringei ) [ 57 ], while another study showed that in chimpanzees, males with higher strength in a proximity network had a higher chance of showing symptoms of respiratory disease, indicating the vital role of the social-proximity network in the spread of the pathogen in the group [ 58 ]. However, this study focused solely on adult males and did not investigate the role of females and juveniles, which can also be important mediators of the spread of pathogens throughout the group [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having observed a positive association between social network and geohelminth infection, we then tested the impact of sampling bias on these results, by including/excluding certain age-sex classes from the analysis. For various reasons, numerous studies have focused on specific age-sex classes rather than the whole social group (Hamilton et al, 2020; Roberts and Roberts, 2020; Sandel et al, 2021; Webber et al, 2016). Through targeted removal of network subsets and subsequent reanalysis, we demonstrated that the original relationship observed using the whole group network becomes insignificant, both in classical statistical terms (i.e., loss of statistical significance) and in absolute quantitative terms, as the model parameter estimates were in some cases considerably lower, to the point where we could not conclude from randomisation tests that the observed effects of sociality on parasitism were different from those expected to arise by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Having observed a positive association between the social network and geohelminth infection, we then tested the impact of sampling bias on these results, by including/excluding certain age-sex classes from the analysis. Numerous studies have focused on specific age-sex classes rather than the whole social group (Hamilton et al, 2020;Roberts and Roberts, 2020;Sandel et al, 2021;Webber et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the same way that pathogens are transmitted from great apes to people, the reverse also occurs, mainly in respiratory diseases [42]. In fact, communities close to NHPs have developed simultaneous outbreaks of respiratory diseases caused by different viruses of human origin [43].…”
Section: New Diseases Transmitted From Humans To Great Apesmentioning
confidence: 99%